Research Opportunities for Application of Gamification Models with VR for Crop Cultivation: A Systematic Literature Review - Suhendi; Murli, Norhanifah (International Journal of Integrated Engineering, 2023)
The learning delivery model in the increasingly developing information technology era and the era of teaching and learning between students and lecturers during the Covid-19 pandemic requires lecturers’ creativity. The application of gamification using virtual reality is an alternative solution that can be applied to fill the saturation of online learning using Google Meeting or Zoom meeting. This review of the literature aims to see how many gamification applications using virtual reality are specifically applied to plant cultivation. The process of obtaining this literature review is based on the systematic literature review (SLR) method. The assessment process is carried out through four online databases based on the keywords gamification and virtual reality. The results obtained are 32 relevant literature on gamification using virtual reality although gamification using virtual reality for plant cultivation is not found and only one paper on forestry only discusses the concept. However, the results of this process become the basic literature for further research on the application of virtual reality gamification in plant cultivation.